2014
DOI: 10.1021/bi4014769
|View full text |Cite
|
Sign up to set email alerts
|

Turnover-Dependent Inactivation of the Nitrogenase MoFe-Protein at High pH

Abstract: Proton uptake accompanies the reduction of all known substrates by nitrogenase. As one consequence, higher pH should limit the availability of protons as a substrate essential for turnover, thereby increasing the proportion of more highly reduced forms of the enzyme for further study. The utility of the high pH approach would appear problematic in view of the observation reported by Pham and Burgess (Biochemistry 32, 13725 (1993)) that the MoFe-protein undergoes irreversible protein denaturation above pH 8.65.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 49 publications
(110 reference statements)
2
29
0
Order By: Relevance
“…In previous studies 28,29,30,31,32 by one of us (RB) we have assigned the alkoxide group of the homocitrate as protonated but have not until now given a complete justification for this as the question of how well the protein environment is described surrounding the homocitrate remained unclear. The only exception to this is the 4ND8 crystal structure, recently published by Rees & Howard et al 85 which is a crystal structure solved under basic (pH 9.5) conditions, where the O-O distance is on average 2.77 Å as shown in Figure 6d. This is in very good agreement with a QM/MM model where the proton is missing (Figure 6d).…”
Section: Protonation State Of Homocitratementioning
confidence: 99%
“…In previous studies 28,29,30,31,32 by one of us (RB) we have assigned the alkoxide group of the homocitrate as protonated but have not until now given a complete justification for this as the question of how well the protein environment is described surrounding the homocitrate remained unclear. The only exception to this is the 4ND8 crystal structure, recently published by Rees & Howard et al 85 which is a crystal structure solved under basic (pH 9.5) conditions, where the O-O distance is on average 2.77 Å as shown in Figure 6d. This is in very good agreement with a QM/MM model where the proton is missing (Figure 6d).…”
Section: Protonation State Of Homocitratementioning
confidence: 99%
“…This experiment hints at a strategy that could be effectively used to increase the biomass activity of an N-deficient biofilm oxidizing oxalate exposed to an unfavourable high pH such as pH 9. As previously highlighted, nitrogenase activity is compromised at high pH (Yang et al, 2014), and this likely imposes severe nitrogen limitation, affecting microbial growth. The exposure to favourable pH conditions increases nitrogenase activity reducing limitations of nitrogen for growth and as a consequence, a rapid increase of biomass can be anticipated.…”
Section: A Continuous Influent Flow Can Facilitate the Maintenance Ofmentioning
confidence: 94%
“…In the absence of an inorganic source of N, the oxalate oxidizing activity recorded in the N-deficient reactor suggested that the microorganisms there would have to fulfil their N requirements plausibly via biological fixation of atmospheric N. It is well known that the enzyme responsible for catalysing the fixation of N is nitrogenase (Hernandez et al, 2009). This enzyme is known to be inhibited when exposed to highly alkaline conditions (Yang et al, 2014). According to Hadfield and Bulen (1969) and Igarashi et al (2005), the pH dependence of nitrogenase activity exhibits a bell-shaped relationship, whereby an optimal activity is at approximately pH 7-8.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, molybdenum and tungsten heterometallic M 3 M'S 4 (M'= transition metal) sulfides have been proposed as models for metalloenzimes [1] or industrial hidrodesulfurization (M'= Ni or Co) catalysts [2,3]. Hidai et al…”
Section: Introductionmentioning
confidence: 99%